From lab to fab : investigating facile and scalable methods of perovskite solar cell fabrication - Lew, Jia Haur (Nanyang Technological University, 2021)
Perovskite solar cells have seen dramatic improvements in terms of device efficiency. In a short span of a decade, the device efficiency improved from 3.8% to beyond 24%. Low cost of precursor materials coupled with highly facile spin coating techniques used to fabricate perovskite solar cells have contributed to the impressive improvement of efficiencies in the short time frame. However, most of perovskite solar cells that reported efficiencies beyond 23% employs a spin-coating technique for cell fabrication, followed by an evaporation step to deposit the contacts. Also, these high efficiency numbers are only recorded on small areas smaller than 1cm2, which has little real-world applications. Furthermore, this spin coating method has high material wastage, and usage of the thermal evaporator limits the throughput required by industrial needs. These scaling issues, coupled with the low stability of the perovskite material in the presence of moisture, remain as one of the main tumbling blocks that hinders the commercialization of this promising technology. An alternative architecture that could pave the pathway towards the commercialization of perovskite solar cells would be the fully printable mesoscopic design employing carbon material as a counter electrode. The mesoscopic layers are printed and sintered, and the device is completed by infiltrating the pores with perovskite precursor solution. This highly scalable and facile method of perovskite solar cell fabrication, coupled with high throughput and little material wastage, seem to offer the best compromise of what it takes to commercialize this promising technology. This architecture offers reasonable efficiencies of up to 15%, offers high scalability to 70cm2 in size. Furthermore, the carbon electrode serves a dual-purpose role of charge collector and extractor, as well as a protective layer against moisture ingression. Like the earlier section, the high efficiencies of fully printable mesoscopic solar cells are reported based on small surface area with large amount of masking. This could lead to erroneous and exaggerated PCE values. In this thesis, systematic experiments have been outlined with the aims to properly evaluate and further improve the performance of the fully printable mesoscopic perovskite solar cell. Firstly, the active area effect on the efficiency, as well as the effect of masking on the device efficiency is being investigated. Secondly, systematic scale up of the printable solar cell is being discussed. A 70cm2 module with 10% PCE values is fabricated. Next, experiments are planned to enhance the device performance. Optimization of additive concentration improved pore filling and device performance. A thinly printed Cu:Niox is introduced as an p-type oxide interlayer between carbon and ZrO2. A well aligned energy level of the p-type oxide with the valence band of the perovskite material should enhance charge extraction, improving device performance. The last part of the chapter also includes preliminary investigation of encapsulation. Various means of encapsulation are discussed. The second part of this chapter discusses about the optimization the patterning process using laser ablation. A combination of encapsulation and laser processes are essential to ensure the translation of perovskite technology from the lab to commercial scale. Finally, the final chapter draws a conclusion and summarizes the thesis. Further works are also being discussed, which will help to facilitate the push towards commercialization of printable perovskite solar cells.